Танцы марионеток: [роман] / Е. Михалкова - Михалкова Елена (Детектив-событие, 2009)
Экземпляры: ф.17 (2021) / Инвентарный номер: 57197 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: М 69 / ББК: 84(2Рос=Рус)6